Effectiveness of Young Papaya Fruit Extract (Carica Papaya L) on Prolactin Hormone and Infant Body Weight - Eko Puji Kaptiyanti, Edining; Sumarni, Sri; Susanto, Edy (Journal of Maternal and Child Health, 2026)
Background: Breast milk is the best nutrition for infants. Successful exclusive breastfeeding during the first six months of life optimizes growth, cognitive development, and strengthens the infant's immune system. Prolactin, which affects breast milk production, remains a barrier to exclusive breastfeeding. One approach is to utilize natural lactagogic ingredients such as unripe papaya (Carica papaya L.). The purpose of this study was to analyze and demonstrate the effectiveness of unripe papaya extract on increasing prolactin levels and infant weight in breastfeeding mothers. Subjects and Methods: This study used a quasi-experimental design with a two-group pretest-posttest design. The study location was the Danasari Community Health Center, Bojong District, Tegal Regency. Data collection was conducted from July to August 2025. The intervention group consisted of 1000 mg/day of unripe papaya extract, UHT milk, and boiled eggs for 7 days, and the control group received nursing care, UHT milk, and boiled eggs for 7 days. The dependent variables studied were prolactin hormone and infant weight, and the independent variables were unripe papaya extract, milk, and boiled eggs. Analysis techniques used were the Wilcoxon test and the Paired Sample T-Test. Results: The average prolactin hormone level in the intervention group after administration of unripe papaya extract was higher (Mean = 199.70; SD = 72.57) than before the intervention (Mean = 174.50; SD = 64.08) and was statistically significant (p = 0.002). The average infant weight in the intervention group after administration of unripe papaya extract was higher (Mean = 5631.50; SD = 987.73) than before the intervention (Mean = 5313.75; SD = 1025.04) and was statistically significant (p = 0.000). Conclusion: Administration of unripe papaya extract has been shown to be effective in increasing prolactin hormone levels in breastfeeding mothers and infant weight.